Heautoscopy, epilepsy, and suicide. Issue 7 (July 1994) - Brugger, P; Agosti, R; Regard, M; Wieser, H G; Landis, T
Abstract : Heautoscopy (the doppelgänger experience), epilepsy, and suicide is a triad primarily known from literary accounts. This paper reports a patient with complex partial seizures who tried to commit suicide during the experience of heautoscopy.